2021
DOI: 10.21203/rs.3.rs-395340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Professional Love in Early Childhood Education: the experience of Aotearoa New Zealand

Abstract: Love is essential for human psycho-social development, in particular in the early years. Just as the love of parents/care-givers and others in the home setting is vital, there is increasing recognition that love is important for infants, toddlers and young children in early childhood education settings (ECES). However, love demonstrated by teaching professionals continues to be under-researched (Dalli 2005; Page 2017a). As a result, educational policy and practice guidelines are still embryonic, or may not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These methods aimed to make them feel welcome and relaxed in the nursery setting. In many studies (e.g., Stewart-MacKenzie, 2021;Page, 2018;Badanes et al, 2012) it has been reported that the acceptance, love and care that children feel, contribute to their smooth adaptation to the ECEC settings and are fundamental to their healthy development. However, the covid-19 restrictions have turned the morning welcome routine into a formal process without the prior interaction between educators and children.…”
Section: Discussionmentioning
confidence: 99%
“…These methods aimed to make them feel welcome and relaxed in the nursery setting. In many studies (e.g., Stewart-MacKenzie, 2021;Page, 2018;Badanes et al, 2012) it has been reported that the acceptance, love and care that children feel, contribute to their smooth adaptation to the ECEC settings and are fundamental to their healthy development. However, the covid-19 restrictions have turned the morning welcome routine into a formal process without the prior interaction between educators and children.…”
Section: Discussionmentioning
confidence: 99%